A comparison of the quantification aspects of human reliability analysis methods in nuclear power plants. (November 2019) - Park, Jooyoung; Arigi, Awwal Mohammed; Kim, Jonghyun
Highlights: This study compared quantification aspects of HRA methods. Four typically-used HRA methods were considered. Seven post-initiators representing OPR1000 type of NPPs in Korea were considered. Eight findings are identified. Abstract: Human reliability analysis (HRA) is a method for evaluating human errors and providing human error probabilities (HEPs) for application in probabilistic safety assessment (PSA). Up to date, there has not been a universally accepted HRA method for estimating HEPs, because such acceptance still has several challenges, including 1) data scarcity for predicting HEPs, 2) limited representation of cognitive aspects of human performance, and 3) significant differences in HRA results from different analysts, even when applying the same method. Some comparison studies were conducted to study differences among the HRA methods, or to select the most suitable method for application in the corresponding fields. However, these studies have several weak points in understanding differences among HRA methods. This study compared quantification aspects of HRA methods. Four typically-used HRA methods were considered. Seven post-initiators having representative conditions for the OPR1000 type of nuclear power plants (NPPs) were analyzed. Then, an investigation verified quantification differences among the HRA methods. As a result, eight findings are described. The result of this study could help HRA practitioners like NPP utilities or regulatory agencies to 1) aid in the selection of the proper method for its intended use or application, 2) estimate ranges of HEPs when using these HRA methods and 3) use this result as a reference of HEPs.